Editorial - Gutiérrez Santana, Lucila (Interpretextos revista semestral de creación y divulgación de las humanidades (Colima), 2025)
This edition arrives at 2025 loaded with words, verses, history and literature by well-known authors, such as Jorge Ibargüengoitia or Alfonso Reyes, but also by others who are not so well-known, such as Lourdes Casal or Elvia Correa; we also present texts that are more related to history, such as “México y sus duendes” or “El estanco de tabacos de la Villa de Colima de Colima”. These, among other articles, are part of the content of the magazine. We invite you to enter these letters that more than a pretext, are an opportunity to get to know Colima, Mexico, and the world.